2008
DOI: 10.1212/01.wnl.0000311389.26145.95
|View full text |Cite
|
Sign up to set email alerts
|

Assessment: Botulinum neurotoxin for the treatment of movement disorders (an evidence-based review) [RETIRED]

Abstract: Objective:To perform an evidence-based review of the safety and efficacy of botulinum neurotoxin (BoNT) in the treatment of movement disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
157
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 456 publications
(162 citation statements)
references
References 79 publications
(36 reference statements)
0
157
0
3
Order By: Relevance
“…Case series indicate that botulinum toxin can not only reduce tics but also associated uncomfortable premonitory sensations and pain [24,25]. Eyeblinking, neck and shoulder tics are the most common tics treated this way.…”
Section: Botulinum Toxin For Ticsmentioning
confidence: 99%
“…Case series indicate that botulinum toxin can not only reduce tics but also associated uncomfortable premonitory sensations and pain [24,25]. Eyeblinking, neck and shoulder tics are the most common tics treated this way.…”
Section: Botulinum Toxin For Ticsmentioning
confidence: 99%
“…Based on the 2008 AAN evidence-based recommendations, the authors found two efficacy trials that would fulfil their criteria as class II studies [Simpson et al 2008]. The first study by Jankovic and Orman provided class II evidence for chemodenervation on blepharospasm [Jankovic and Orman, 1987].…”
Section: Onabotulinumtoxina (Botox)mentioning
confidence: 99%
“…Two companion articles review the use of BoNT for other conditions: one on headache, back pain, autonomic, and urologic disorders, 9 and another on selected movement disorders, including blepharospasm, hemifacial spasm, cervical dystonia, focal limb dystonia, laryngeal dystonia, and tics and tremor. 10 While brief mention is made of other treatments for the covered indications, discussion of detailed evidence supporting their efficacy is beyond the scope of this article.…”
Section: Description Of the Analytical Pro-cessmentioning
confidence: 99%